KELELAWAR SEBAGAI SUMBER INSPIRASI DALAM PENCIPTAAN SENI TEKSTIL - Arief Satriyo Wibowo (Corak : Jurnal Seni Kriya, 2017)
Bats are flying mammals, now these animals have several species of bats that are endangered. Due to the destruction of the original habitat of the bark in the forest that becomes the function, the exploitation of karst areas (lime), the use of pesticides on agricultural land, hunting and excessive consumption. Many functions of bat ecology therefore in need of efforts in controlling the population of bats. The idea of the creation of this textile artwork originated from personal experience, natural factors, sympathy and empathy for the preservation of fauna, namely bat animals. All of which are then transformed into non-functional work forms which furthermore want to bring the values of change so that the celebration can know it and finally feels may be able to understand the message delivered. The process of creating works on non functional techniques used in the form of nylon nylon thread wire on top of the wire. Keywords: bats, non-functional, creation textiles  Kelelawar merupakan hewan mamalia terbang, sekarang hewan ini terdapat beberapa spesies kelelawar yang statusnya terancam punah. Akibat rusaknya habitat asli kelalawar di hutan yang menjadi alih fungsi, eksploitasi wilayah karst (kapur), penggunaan pestisida pada lahan pertanian, perburuan serta pengkonsumsian yang berlebihan. Banyak fungsi ekologi kelelawar oleh karena itu di perlukan usaha-usaha dalam mengendalikan populasi kelelawar. Ide penciptaan karya seni tekstil ini berawal dari pengalaman pribadi, faktor alam, rasa simpati dan empati terhadap kelestarian fauna yaitu hewan kelelawar. Kesemua yang kemudian ditransformasikan ke bentuk karya non fungsional yang selanjutnya ingin membawa nilai-nilai perubahan sehingga khlayakan dapat mengetahuinya dan akhirnya dirasa mungkin dapat mengerti akan pesan yang disampaikan. Proses penciptaan karya pada non fungsional tehnik yang digunakan berupa lilit benang nilon hank di atas kawat. Kata kunci: kelelawar, non fungsional, penciptaan tekstil